Handbook of industrial engineering : technology and operations management - Salvendy, Gavriel, 1938- (Wiley, 2001)
The Handbook of Industrial Engineering, Third Edition is an immensely useful one-stop resource for industrial engineers and technical support personnel in corporations of any size; continuous process and discrete part manufacturing industries; and all types of service industries, from healthcare to hospitality, from retailing to finance.